Parenthood and Partnerhood in the Context of Involuntary Childlessness and Assisted Reproduction in Greece. (May 2017) - Chatjouli, Aglaia; Daskalaki, Ivi; Kantsa, Venetia
Ta en oiko mi en dimo is a popular Greek proverb meaning that whatever happens at household [ oikos ] should not be exposed into public [ dimos ]. In the Greek cultural context sexuality, reproduction, family relations belong to the realm of private domesticity. In this paper we trace the way women and men in Greece resituate themselves towards their reproductive desires and decisions, towards medicalized reproduction and towards each other, when in the context of involuntary childlessness, infertility and ART use, reproduction moves outside the body and the private sphere of the household and becomes part of the public sphere exemplified in state laws, doctor's decisions, hospital laboratories, IVF forums. Drawing from the research project (In)FERCIT and based on 130 semi-structured interviews of both women and men the paper explores the shifts related to parenting, the imagining and making of a family, the couple, in the context of neoliberal reproductive potentialities. Which relationships and practices change through the ongoing challenges of infertility and the experience of ART? What is kept within the couple and what is shared with others (family members, friends, strangers, experts)? What is the significance of reproductive socialities in managing the demands of infertility within an ever-increasing intensification of parenthood? How does this challenging context reinforces or weakens the couple's relationship, their reproductive agency and desire? Finally we explore how proper parenthood but also proper partnerhood are constructed in Greece following local demands regarding family making and localized medicalization of reproduction.